Measuring Customer Loyalty and Satisfaction of Bank Bantul Using CRM and Service Quality - Heri Sutanto; Siti Dyah Handayani; Susanto Susanto (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to analyze and describe the effects of the service quality and customer relationship management at PD BPR Bank Bantul on the customer satisfaction and loyalty. The object of this study is PD BPR Bank Bantul, while the subjects of the study are customers taking the SMEs credit offered by the Bank. Method of analysis used in this study was Structural Equation Modelling (SEM) with the help of the AMOS program. The number of respondents was 170, taken using purposive sampling. The criteria for the sampling are as follows: the respondents are taking the SME’s credit at PD BPR Bank Bantul, residents in Bantul Regency, who are individual customers, who have been 2 years or more customer and have done 2 or more credit transactions. Data was collected through questionnaires distributed directly to the respondents and through the google form. Based on the results of the analysis, show that service quality has no significant effect on customer satisfaction, customer relationship management has a positive and significant effect on customer satisfaction, service quality has no a positive and significant effect on customer loyalty, customer relationship management has a positive and significant effect on customer loyalty and customer satisfaction has a positive and significant effect on customer loyalty. In conclusion this study accepts 3 hypotheses and rejects 2 hypotheses.